2022
DOI: 10.1024/0301-1526/a000989
|View full text |Cite
|
Sign up to set email alerts
|

Transient perivascular inflammation of the carotid artery (TIPIC) syndrome

Abstract: Summary: Background: The Transient Perivascular Inflammation of the Carotid artery (TIPIC) syndrome is presumably a very rare disease characterized by a local transient inflammation of the tissue around the carotid artery. Its pathophysiology remains unknown. We performed an updated study of TIPIC syndrome cases in the setting of a multinational collaborative study. Methods: This study was conducted as an observational multinational retrospective individual patient level cohort study. Information from all know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 22 publications
1
32
1
11
Order By: Relevance
“…Beim TIPIC Syndrom besteht neben akuten, meist einseitigen Schmerzen im Halsbereich bildmorphologisch eine exzentrische perivaskuläre Infiltration der Arteria carotis (▶ abb. 2) [23,24]. Die Diagnose setzt den Ausschluss einer anderen vaskulären oder nichtvaskulären Ursache voraus.…”
Section: Tipic Syndromunclassified
See 2 more Smart Citations
“…Beim TIPIC Syndrom besteht neben akuten, meist einseitigen Schmerzen im Halsbereich bildmorphologisch eine exzentrische perivaskuläre Infiltration der Arteria carotis (▶ abb. 2) [23,24]. Die Diagnose setzt den Ausschluss einer anderen vaskulären oder nichtvaskulären Ursache voraus.…”
Section: Tipic Syndromunclassified
“…Die Diagnose setzt den Ausschluss einer anderen vaskulären oder nichtvaskulären Ursache voraus. In Fallserien kommt es innerhalb von 14 Tagen meist zu einer deutlichen Besserung, spontan oder unter Therapie mit Acetylsalicylsäure oder anderen Analgetika mit antiphlogistischer Wirkung [23,24]. Es muss erwähnt werden, dass einzelne Patienten in einer Fallserie [23] Glukokortikoide erhielten oder unter einer Autoimmunerkrankungen litten, die zeitgleich mit dem Auftreten des TIPIC-Syndroms, exazerbiert war.…”
Section: Tipic Syndromunclassified
See 1 more Smart Citation
“…Intermittent slightly elevated C-reactive protein and erythrocyte sedimentation rate were observed up to 1 Although the present study is limited by a small sample size, demographic and clinical findings of our case series are comparable to other recent studies, but with some differences, such as higher rates of preexisting autoimmune disorders, cardiovascular risk factors, posttraumatic events, or local neck swelling. 1,2,4 Additionally, all of our investigated patients had hypercholesterolemia at disease onset. Those findings may support (auto-) inflammatory but also atherosclerotic implications in the development of TIPIC syndrome, as previously reported.…”
mentioning
confidence: 94%
“…A recent multicenter retrospective study of 72 patients with TIPIC syndrome confirmed the benign nature of this disorder and that recurrence may occur in up to 20% of cases. 3 However, TIPIC pathophysiology and triggers remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%